2021
DOI: 10.1002/elsc.202100009
|View full text |Cite
|
Sign up to set email alerts
|

Efficient phenol degradation by laccase immobilized on functional magnetic nanoparticles in fixed bed reactor under high‐gradient magnetic field

Abstract: Enzymatic degradation of emerging contaminants has gained great interest for the past few years. However, free enzyme often incurs high costs in practice. The immobilized laccase on the polyethylenimine (PEI)‐functionalized magnetic nanoparticles (Fe3O4–NH2–PEI–laccase) was fabricated to efficiently degrade phenolic compounds continuously in a newly fixed bed reactor under a high‐gradient magnetic field. The degradation rate of continuous treatment in the bed after 18 h was 2.38 times as high as that of batch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In another work, the same group developed a new fixed-bed reactor to achieve continuous decomposition of phenolic compounds in a high-gradient MF [ 69 ]. They further investigated the different effects between continuous and pulse treatments with AMF and found that the rate of continuous treatment for 18 h resulted in a 2.38 times faster reaction rate than the pulse treatment for 6 cycles.…”
Section: Practical Applications Of Magneto-mechanical Actuationsmentioning
confidence: 99%
“…In another work, the same group developed a new fixed-bed reactor to achieve continuous decomposition of phenolic compounds in a high-gradient MF [ 69 ]. They further investigated the different effects between continuous and pulse treatments with AMF and found that the rate of continuous treatment for 18 h resulted in a 2.38 times faster reaction rate than the pulse treatment for 6 cycles.…”
Section: Practical Applications Of Magneto-mechanical Actuationsmentioning
confidence: 99%
“…Sufficient residence time was important to make sure that phenol solution was interacting with the immobilized laccase to achieve efficient catalysis. Due to high flow rate, the phenol degradation efficiency of laccase was decreased in the continuous treatment process (Xia et al, 2021).…”
Section: Effect Of Volumetric Feeding Rate On Bpa Bioremediation Effi...mentioning
confidence: 99%
“…The study showed that the reactor achieved 100% degradation of phenol during continuous operation of the bioreactor when the phenol concentration was 200 mg/dm 3 and the flow rate was less than 10 cm 3 /min. Xia et al [ 147 ] immobilized laccase on polyethyleneimine-functionalized magnetic nanoparticles, which were filled with magnetic laccase in a novel fixed-bed bioreactor. The study demonstrated that, after continuous degradation of phenolic compounds for 18 h, the degradation rate in the reactor was 2.38 times that of the batch treatment, and, under optimal operating conditions, the fixed-bed reactor still maintained a phenol degradation rate of more than 70% after continuous operation for 48 h.…”
Section: Applications Of Immobilized Biomass Materials In Bioreactormentioning
confidence: 99%